A new species of the genus Aporcelinus Andrássy, 2009 (Nematoda, Dorylaimida, Aporcelaimidae) from Costa Rica - Varela-Benavides, Ingrid; Peña-Santiago, Reyes (Zootaxa, 2018)
A new species of the genus Aporcelinus, A. elongicaudatus sp. n., collected from natural habitats of Costa Rica, is described and illustrated. The new species is characterized by its 0.92–1.05 mm long body, lip region offset by weak constriction and 15 µm broad, odontostyle 15–18 µm or 1.0–1.2 times the lip region diameter, neck 270–300 µm long, pharyngeal expansion 130–150 µm long or 45–55% of total neck length, uterus 33–41 µm long or 0.70–0.85 times the corresponding body diameter (but certainly longer), vulva transverse (V = 49–51), and tail conical elongated (45–71 µm, c = 14–22, c’ = 2.0–3.2) and dorsad bent.